2014
DOI: 10.1002/2013jd020710
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of precipitation stable oxygen isotope variability in an alpine setting, Snowy Mountains, Australia

Abstract: Natural archives that preserve a stable isotopic signature are routinely used to reconstruct palaeoenvironmental conditions. Isotopic values of precipitation are known to be influenced by factors such as the amount and type of precipitation, moisture pathway, landscape and terrain factors, and processes associated with precipitation formation and deposition. This study investigates oxygen isotopic variability using real-time rain and snow precipitation data from a moderate altitude (<2250 m above sea level), S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In a similar way, event precipitation isotope analyses conducted by Callow et al (2014) identified significant synoptic-type variability in the isotopic signature of precipitation in the Snowy Mountains. The results of our study further support the dominance of moisture-source pathways in controlling isotopic variability in this region.…”
Section: Discussionmentioning
confidence: 70%
“…In a similar way, event precipitation isotope analyses conducted by Callow et al (2014) identified significant synoptic-type variability in the isotopic signature of precipitation in the Snowy Mountains. The results of our study further support the dominance of moisture-source pathways in controlling isotopic variability in this region.…”
Section: Discussionmentioning
confidence: 70%
“…Many studies have investigated the spatial variability in the isotopic composition of precipitation at the mesoscale (100–1,000 km 2 ) and larger scale (up to the regional and continental scale). They typically found a large spatial variability in the isotopic composition of precipitation that could be explained by the orographic effect, the amount effect, sub‐cloud evaporation, moisture recycling, and differences in the vapor source (e.g., Bortolami, Ricci, Susella, & Zuppi, ; Pionke & De Walle, ; Ersek, Mix, & Clark, ; Crawford, Hughes, & Parkes, ; Callow, McGowan, Warren, & Speirs, ; Tekleab, Wenninger, & Uhlenbrook, ; Peng, Chen, Zhan, Lu, & Tong, ; Kong & Pang, ; Giustini, Brilli, & Patera, ; Delavau, Stadnyk, & Holmes, ; Krklec, Domínguez‐Villar, & Lojen, ). Studies on the isotopic composition of precipitation in small catchments (<10 km 2 ) exists as well (e.g., Gou et al, ; Qu et al, ) but very few of these studies report the observed spatial variability (or data).…”
Section: Reported Spatial Variability In the Isotopic Compositionmentioning
confidence: 99%
“…The Yarrangobilly limestone is a massive Silurian formation located in the subalpine area of the northern region of Kosciusko National Park, southeastern Australia (Figure ). The region may provide critical data to understand the palaeo‐climate of both southeastern Australia and the Southern Hemisphere, due to the location of the caves complex, which experiences precipitation sourced from southern mid‐latitudes to the tropics (Callow, McGowan, Warren, & Speirs, ; Theobald, McGowan, Speirs, & Callow, ). Despite this, there is very little published research conducted on the speleothems and associated hydrology of this region (see Markowska et al, ; Spate, Jennings, Ingle Smith, & James, ; Webb et al, ).…”
Section: Study Region and Methodsmentioning
confidence: 99%